Polarization and angular peculiarities of IR emission of thin film semiconductor structures - Kollyukh, O.G.; Liptuga, A.I.; Morozhenko, V.O.; Pipa, V.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
In this paper thermal radiation from plane-parallel semiconductor layers was investigated. Shown is that spectra of thermal radiation from structures has an oscillating character caused by multi-beam interference. It was shown that the density of thermal radiation, at its interference maximum, can be equal to half the density of thermal radiation from a blackbody source, at the same time at the interference minimum the value approached practically zero. In addition, the angular dependence of thermal radiation does not obey the Lambert law and demonstrates a non-monotonic character with clearly pronounced extrema.